Meat production of the Boutsko breed of ewes in Epirus - FOLINAS (Γ. Σ. ΦΩΛΙΝΑΣ) G. (Journal of the Hellenic Veterinary Medical Society, 2018)
A flock of 244 hill sheep of the indigenous Boutsko breed of Epirus (NW of Greece), 1-6 years old, reared under a transhumance system was used to study the growth of suckled lambs and their carcass quality. The results of the study have been summarized as follows: 1) Birth liveweight of lambs was 4.3 ±0.12 Kg (single males), 3.9±0,10 Kg (single females) (P<0.05) and 3.6±0.08 Kg (twins) (P<0.01). The corresponding liveweights at slaughterwerell.2±0.25Kg, 10.7±0.23Kg and 11.3±0.36 Kg and their carcass weights 7.1 ±0,17 Kg, 7.1±0,17 and 6.9 ±0.26 Kg. 2) The conclusion drawn from the results of this study is that the Boutsko breed is a useful and well adapted genotype of sheep. However, its meat productivity is very low and could be improved by further within breed selection and/or grazing on improved pasture.